Executive compensation and the cost of debt - Kabir, Rezaul; Li, Hao; Veld-Merkoulova, Yulia V. (Journal of Banking & Finance, 2013)
This study examines how different components of executive compensation affect the cost of debt. We find that debt-like and equity-like pay components have differing effects: an increase in defined benefit pensions is associated with lower bond yield spread, while higher share holdings lead to higher spreads. In addition, we find that stock options have a mixed impact on the cost of debt whereas cash bonus has no significant impact. Overall, our results indicate that corporate bondholders are fully aware of both risk-taking and risk-avoiding incentives created by various executive pay components.